Anatomy of Cleome rutidosperma DC. (Cleomaceae) Ovary Development in Mataram City - Lestari, Zuhara Dwi; Aeni, Quratul Puspa; Safitri, Zalianty Dwinur; Gunawan, Satria; Pratami, Windi; Nur Shopya Affifaturrahmah; Miranti, Suci; Mulyaningsih, Tri (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2025)
Cleome rutidosperma is one of the species that belong to famili Cleomaceae and ordo Brassicales.  The purpose of this research is to observe the ovary development of C. rutidosperma and analyse the differences in each growth phase. C. rutidosperma is belong to Brassicales order. Ordo Brassicales is well known for having cleistogamy type of flowers. This research is going to prove C. rutidosperma belongs to cleistogamy or chasmogamy pollination type. However, the best solution is to research until a new study is obtained that discusses the development of C. rutidosperma ovaries and C. rutidosperma flower type. The results of this study can also open new insights and open further research. The results shows in first phase the ovaries were already in the early developmental stage such as protrusions. This development continues to complete and expand its structure. Some of these include the growth of the funiculus which continues to change until it reaches a phase where the funiculus already appears to fully support the ovule. In the last two phases, it can also be seen that structures such as the inner integument and integument begin to appear. The development has greatly increased from the previous phase.